International assessment of inter‐ and intrarater reliability of the International Frontal Sinus Anatomy Classification system. Issue 1 (14th September 2018) - Villarreal, Ricardo; Wrobel, Bozena B.; Macias‐Valle, Luis F.; Davis, Greg E.; Prihoda, Thomas J.; Luong, Amber U.; McMains, K. Christopher; Weitzel, Erik K.; Yao, William C.; Brunworth, Joe; Clark, David W.; Nair, Salil; et al.
Abstract : Background: Inconsistencies in the nomenclature of structures of the frontal sinus have impeded the development of a validated "reference standard" classification system that surgeons can reliably agree upon. The International Frontal Sinus Anatomy Classification (IFAC) system was developed as a consensus document, based on expert opinion, attempting to address this issue. The purposes of this study are to: establish the reliability of the IFAC as a tool for classifying cells in the frontal recess among an international group of rhinologists; and improve communication and teaching of frontal endoscopic sinus surgery (ESS). Methods: Forty‐two computed tomography (CT) scans, each with a marked frontal cell, were reviewed by 15 international fellowship‐trained rhinologists. Each marked cell was classified into 1 of 7 categories described in the IFAC, on 2 occasions separated by 2 weeks. Inter‐ and intrarater reliability were evaluated using Light's kappa (κ), the interclass correlation coefficient (ICC), and simple proportion of agreement. Results: Interrater reliability showed pairwise κ values ranging from 0.7248 to 1.0, with a mean of 0.9162 (SD, 0.0537). The ICC was 0.98. Intrarater reliability showed κ values ranging from 0.8613 to 1.0, with a mean of 0.9407 (SD, 0.0376). The within‐rater ICC was 0.98. Conclusion: Among a diverse sample of rhinologists (raters), there was substantial to almost perfect agreement between raters, and among individual raters at different timepoints. The IFAC is a reliable tool for classification of cells in the frontal sinus. Further outcome studies are still needed to determine the validity of the IFAC.